The Difference Of Javanese And Indonesian Vocabularies In Preschool Age Children - Windiarti Dwi Purnaningrum; Muryanti Muryanti (Poltekkes Kemenkes Surakarta, 2021)
Background: Vocabulary is an important component of language aspect in children. Vocabulary mastery is a good predictor to see the language ability of children in further age. Speaking using more than one language gives children a broader experience to access language learning. This research was conducted to see the difference of vocabularies in Javanese and Indonesian languages. Methods: The research was conducted using cross-sectional design. Data collection was conducted by distributing questionnaire to parents. The sample design used was total sampling. Data collection was conducted on April-September 2019. Results: The result of analysis using Mann Whitney test shows that there is a difference of vocabularies between Javanese and Indonesian languages. Variance test shows that Javanese vocabularies are higher in quantity than Indonesian vocabularies. Conclusion: There is a difference of vocabularies between Indonesian and Javanese. The use of dominant language in daily life putatively contributes to the findings of research. Broader exploration should be conducted to see the comparison between first and second languages.